Voltage Drop Mitigation Strategy Through Reactive Power Compensation on the KTB-03 GI Kota Bangun Outgoing Network - Rendy Artha Kusuma Salempang (PT Publikasiku Academic Solution, 2025)
Voltage drop is one of the main problems in the electric power distribution system, especially in long networks such as the Outgoing KTB-03 Substation in Kota Bangun. This network serves an area with a distribution distance of up to 166 km, which causes an increase in resistance and reactance thus impacting the voltage quality at the network end. This study aims to analyze existing voltage conditions, evaluate the effectiveness of installing shunt capacitors and the construction of 20 kV substations, as well as providing simulation-based technical recommendations to improve the stability and efficiency of power distribution. The method used was a power flow simulation using PSSE (Power System Simulator for Engineering) software, with a voltage stability and PV curve analysis approach to see the effect of network length on voltage and reactive power. The simulation results showed that a 20 kV (GI) substation was the most effective solution for maintaining system voltage stability, with a maximum deviation of only 0.9 V. Meanwhile, the B-Shunt capacitor acted as a local compensation that improved power efficiency and quality, although the effect was systemically limited. Installation of capacitors in the center of the 10.5 Mvar network reduces the voltage deviation in the central area but is still high at the end of the 3.7 kV network, while installation at the end of the network of 3.8 Mvar lowers the end deviation to 2.9 kV but does not resolve the deviation in the center of the network. The combination of capacitors at the center and end of 2.9–3.4 Mvar results in a more even distribution of deviations at each point of the measurement location but the value of the end deviation is still high at 2.8 kV. A more stable and effective solution, the new 20 kV (GI) substation has a significant advantage with a maximum deviation of only 0.9 V, indicating that the system is more controlled and has better voltage regulation. This method is the main recommendation to improve the voltage and reliability of the system in the KTB-03 distribution network.